2015
DOI: 10.4314/mmj.v27i3.3
|View full text |Cite
|
Sign up to set email alerts
|

Environmental risk factors for oesophageal cancer in Malawi: A case-control study

Abstract: AimThere is a high burden of oesophageal cancer in Malawi with dismal outcomes. It is not known whether environmental factors are associated with oesophageal cancer. Without knowing this critical information, prevention interventions are not possible. The purpose of this analysis was to explore environmental factors associated with oesophageal cancer in the Malawian context. MethodsA hospital-based case-control study of the association between environmental risk factors and oesophageal cancer was conducted at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
50
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 28 publications
(28 reference statements)
6
50
1
1
Order By: Relevance
“…Epidemiologic evidence demonstrated a number of risk factors for esophageal cancer, such as age, gender, alcohol drinking, tobacco smoking, obesity, chronic gastroesophageal reflux disease, dietary carcinogens, and insufficiencies of micronutrient consumption [3,4,5], among which dietary factors may play a more important role [6]. Accordingly, chemopreventive agents for esophageal cancer have attracted great attention, including vitamin C, vitamin E, carotenoids, and various minerals [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiologic evidence demonstrated a number of risk factors for esophageal cancer, such as age, gender, alcohol drinking, tobacco smoking, obesity, chronic gastroesophageal reflux disease, dietary carcinogens, and insufficiencies of micronutrient consumption [3,4,5], among which dietary factors may play a more important role [6]. Accordingly, chemopreventive agents for esophageal cancer have attracted great attention, including vitamin C, vitamin E, carotenoids, and various minerals [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…80 Wood burning for heating and cooking has been associated with ESCC in Africa, Iran, and Brazil. 82 This may be related to increased exposure to polycyclic aromatic hydrocarbons. 83 …”
Section: Esophageal Squamous Cell Carcinomamentioning
confidence: 99%
“…76 Although several nonendoscopic techniques to obtain esophageal cytology exist, these techniques have a sensitivity of only 24% to 47% for dysplasia-cancer and 18% to 44% for cancer, making them unsuitable for screening. 82 Very few studies looked at serum biomarkers but those that exist suggest these could be used in the future. 82 …”
Section: Esophageal Squamous Cell Carcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…Mlombe et al's case-control study reported in the current issue is, to my knowledge, the first systematic attempt to answer this question locally. 9 There are other big studies in this area within the sub-Saharan African region, supported by the International Agency for Research on Cancer (IARC) and NIH, for which results are awaited. The country has seen the establishment of the head and neck surgery discipline at Queen Elizabeth Central Hospital (QECH).…”
Section: Research Capacitymentioning
confidence: 99%